Water-retaining polymer as a soil conditioner in cowpea under water stress - Lopes, Marilia Barcelos Souza; Barros, Helio Bandeira; Chagas Júnior, Aloísio Freitas; Santos, Manoel Mota dos; Silva, Niléia Cristina da; Fidelis, Rodrigo Ribeiro (Comunicata Scientiae, 2019)
Cowpea is no longer a family-oriented crop. Today it is cultivated by medium and large farmers in the North and Northeast, due to their adaptation to edaphoclimatic conditions. The objective of this work was to evaluate the efficiency of hydrogel utilization in the retention and availability of water for the development and production of Cowpea beans when subjected to water stress. The experiment was conducted in a randomized block design with four replications in a 5 x 2 factorial scheme, with five concentrations (0, 5, 10, 15 and 20 kg ha-1) and two sources of hydrogels (Hydroplan-EB HyC and Polim-Agri). The cowpea cultivar used was BRS Vinager. The following characteristics were evaluated: number of pods per plant; Number of grains per pod; Pod length: one hundred grain mass and grain yield. The data were submitted to analysis of variance, with the application of the test F. Regression analysis was performed with the help of the SISVAR computer system. The use of hydrogel was an alternative to reduce losses resulting from the action of water stress; the concentrations of hydrogels between 15 and 18 kg ha-1 resulted in higher number of pods per plant, number of grains per pod, the mass of one hundred grains and yields of grains.